1992
DOI: 10.1159/000177707
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Iodine Status among Adults

Abstract: To evaluate the iodine status of Dutch adults we used three different iodine status indicators, namely urinary 24-hour iodide excretion (I/24 h), iodide/creatinine ratio in 24-hour urine samples (I/Cr) and 24-hour iodide excretion per kilogram body weight (I/kg). Additionally, the habitual daily iodine intake was calculated. Men had higher mean I/24 h and mean iodine intake than women. No differences between men and women were found for mean I/Cr and mean I/kg. Relatively high (≧ 18 %) prevalences of low value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In 1981, in Brielle, the Netherlands, a preva lence of habitual low iodine intake of 31 and 50% among adult men and women, respec tively, was found [4], However, that study was conducted before the KI content of bread salt was increased in 1982.…”
Section: Present Iodine Intakementioning
confidence: 99%
“…In 1981, in Brielle, the Netherlands, a preva lence of habitual low iodine intake of 31 and 50% among adult men and women, respec tively, was found [4], However, that study was conducted before the KI content of bread salt was increased in 1982.…”
Section: Present Iodine Intakementioning
confidence: 99%
“…Philips et al (32) It should be pointed out that there are some controversies regarding the units in which iodine urinary excretion should be expressed. Some data reported excretion relative to creatinine excretion, others on the basis of 24-hr urine collection or iodide excretion per kilogram body weight (22). Our data showed clearly that due to large variations in iodine excretion, the assessment of iodine in urine should be adjusted for creatinine excretion (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Numerous studies have shown that daily urine iodine excretion can be accepted as a satisfactory index of iodine intake (4,5,21,22), but there are limited data on iodine concentrations after exposure to excess iodine. Grasso et al (29) reported high concentrations (more than 1000 pg 1/g creatinine) of iodine in the urine of patients admitted to the hospital for nonthyroidal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine is widely used to estimate iodine status in subjects with dietary iodine deficiency, and the guidelines for minimum iodine concentrations in urine have been already established (21,22). Nevertheless, data on iodine levels in urine are scarce.…”
mentioning
confidence: 99%